LUGAR DE HARVEY EN LA HISTORIA DEL METODO CIENTIFICO DE LA BIOLOGIA - IZQUIERDO, JOSE JOAQUIN (ESCUELA DE MEDICINA, 1944)
A general account of a scientific expedition sponsored by Guanos y Fertilizantes de Mexico, SA The author was the biologist of the technical commission that travelled 5,000 miles on the 300-ton motorboat "Gracioso," in Apr, May, and June of 1944, to vi
AN ESC NAC CIENC BIOL
Keywords: LUGAR, HARVEY, HISTORIA, METODO CIENTIFICO, BIOLOGIA; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL